Modifying the electrical behaviour of polypropylene/carbon nanotube composites by adding a second nanoparticle and by annealing processes - H. Palza; C. Garzon; O. Arias (eXPRESS Polymer Letters, 2012)
The effect of different nanoparticles on the geometrical percolation transition of multi-wall carbon nanotubes (CNT) in polypropylene (PP) composites was studied. Our results show that the electrical conductivity of PP/CNT composites (around 2 vol%) can be tuned depending on the characteristic of the third component. Non-conductive layered silica fillers disrupt the CNT percolated network reducing the electrical conductivity of the composite. Spherical nanoparticles otherwise, either copper metal or silica-based, decrease the percolation threshold down to 0.5 vol% of CNT. These results cannot be explained by previous theories about the effect of a second particle on the electrical behaviour of polymer/CNT composites such as the interparticle bridging or the excluded volume. The effect of annealing in the melt was further analyzed and our results show that depending on the concentration and the type of filler, the electrical conductivity of the composites can be increased several orders of magnitude.